Do as I Say or Do as I Do? How Social Relationships Shape the Impact of Descriptive and Injunctive Norms of Voting. Issue 4 (17th October 2021) - Fieldhouse, Edward; Cutts, David
Abstract: Social norms play an important role in our understanding of why people vote, yet very little is known about the relative importance of descriptive and injunctive norms for voter turnout or how normative influence is affected by the political and social relationship between citizens. Using political discussion network data from the British Election Study, this article examines the joint effect of descriptive and injunctive norms on turnout. It demonstrates that citizens follow the example of those closest to them (descriptive norms), especially their partner, but they also respond to social approval of voting from political discussants regardless of the nature of their relationship.